Forerunning value mechanics in value science and theory 2 and 3 : the discovery, verification, and justification of the model of universality of value and its sensitivity /: the discovery, verification, and justification of the model of universality of value and its sensitivity. (2020) - Dornyo, Wisdom Yao
No abstract available